Genome Sequencing Analysis of Scleromitrula shiraiana, a Causal Agent of Mulberry Sclerotial Disease With Narrow Host Range - Lv, Zhiyuan; He, Ziwen; Hao, Lijuan; Kang, Xin; Ma, Bi; Li, Hongshun; Luo, Yiwei; Yuan, Jianglian; He, Ningjia (Frontiers in Microbiology, 2021)
Scleromitrula shiraiana is a necrotrophic fungus with a narrow host range, and is one of the main causal pathogens of mulberry sclerotial disease. However, its molecular mechanisms and pathogenesis are unclear. Here, we report a 39.0 Mb high-quality genome sequence for S. shiraiana strain SX-001. The S. shiraiana genome contains 11,327 protein-coding genes. The number of genes and genome size of S. shiraiana are similar to most other Ascomycetes. The cross-similarities and differences of S. shiraiana with the closely related Sclerotinia sclerotiorum and Botrytis cinerea indicated that S. shiraiana differentiated earlier from their common ancestor. A comparative genomic analysis showed that S. shiraiana has fewer genes encoding cell wall-degrading enzymes (CWDEs) and effector proteins than that of S. sclerotiorum and B. cinerea, as well as many other Ascomycetes. This is probably a key factor in the weaker aggressiveness of S. shiraiana to other plants. S. shiraiana has many species-specific genes encoding secondary metabolism core enzymes. The diversity of secondary metabolites may be related to the adaptation of these pathogens to specific ecological niches. However, melanin and oxalic acid are conserved metabolites among many Sclerotiniaceae fungi, and may be essential for survival and infection. Our results provide insights into the narrow host range of S. shiraiana and its adaptation to mulberries.